Sleep as a recovery tool for elite athletes - Samuels, C.; James, L. (ASPETAR Sports Medicine Journal, 2015)
We know from decades of research that sleep is important for human performance1-3. So, why would we even think about screening athletes when it comes to sleep? Why not just apply basic principles of sleep and generalize from the research that`s been done in other areas such as law enforcement4-7, the military8-11 or aviation12-15? As a result of this research and knowledge athletes, coaches, sport medicine physicians and trainers are interested in understanding the relationship of sleep to training, recovery and performance in athletes. The complicating factor is that athletes, and elite athletes in particular, are very different than the average individual or members of occupational groups such as law enforcement and the military, on whom prior research is based. Athletes have unique physical and mental demands, have to accommodate rigorous competition and training schedules, and have to adapt to difficult travel regimes. So we have to be careful and specific about applying what we know about sleep to athletes. There is a clear need for developing valid, reliable tools to screen and monitor athlete sleep behaviours as the basis for understanding and developing effective interventions.